2015
DOI: 10.11648/j.aff.20150405.12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mycorrhiza Fungi from Grassland Rhizosphere and Liquid Organic Fertilizer to the Growth and Yield of Sweet Corn on Ultisols in South Konawe, Indonesia

Abstract: Abstract:This research was conducted in the Abenggi of village, District of Landono, Regency of South Konawe, Province of Southeast Sulawesi and Laboratory of the Faculty of Forestry and Environmental Science Halu Oleo University Kendari, Indonesia took place from November, 2014 untill April, 2015. This study aims to determine the effect of mycorrhiza fungi from granssland and liquid organic fertilizer to the growth and yield of sweet corn on Ultisols Abenggi. This research is compiled using a randomized block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The results research [7] show that mycorrhiza fungi application can increase maize production ranging from 7.90 to 8.60 tons ha -1 compared to not using mycorrhiza fungi as 5.50 tons ha -1 . Likewise the research results of [8] showed that the application of mycorrhiza fungi at a dose of 40 g/planting hole gave the best results on the growth and production of sweet corn in dry marginal land. While the use of organic fertilizer at a dose of 22.5 kg/plot gives the best results on the dry weight of corn plants [9] and causes a shift in the dominance of weed species [10].…”
Section: Introductionmentioning
confidence: 93%
“…The results research [7] show that mycorrhiza fungi application can increase maize production ranging from 7.90 to 8.60 tons ha -1 compared to not using mycorrhiza fungi as 5.50 tons ha -1 . Likewise the research results of [8] showed that the application of mycorrhiza fungi at a dose of 40 g/planting hole gave the best results on the growth and production of sweet corn in dry marginal land. While the use of organic fertilizer at a dose of 22.5 kg/plot gives the best results on the dry weight of corn plants [9] and causes a shift in the dominance of weed species [10].…”
Section: Introductionmentioning
confidence: 93%
“…There were also findings on mycorrhiza positively influencing plant growth by [18,19] which where AMF was proven to be effective in increasing the growth and yield of soybean plants as well as increasing the efficiency of phosphate fertilizer utilization. Therefore, it is necessary to conduct research to analyze the effect of mycorrhizal application on the growth and production of soybeans planted in various agroecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…According to Miftakhus and Titiek (2018), the need for peanuts to increase is not offset by high production, so the supply of peanuts is reduced. Halim et al (2015) reported that low plant production causes low soil fertility, especially in Ultisol soils with low cation exchange capacity of granite, sediments and tuffs. Therefore, efforts are needed to increase soil fertility to improve the production of groundnut with input technology that is environmentally friendly and based on bio-organic fertilizer from mycorrhiza fungi and cow manure fertilizer.…”
Section: Introductionmentioning
confidence: 99%